2020
DOI: 10.2196/21931
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Trends in Publications on Clinical Cancer Research in Mainland China from the Surveillance, Epidemiology, and End Results (SEER) Database: Bibliometric Study

Abstract: Background The application of China’s big data sector in cancer research is just the beginning. In recent decades, more and more Chinese scholars have used the Surveillance, Epidemiology, and End Results (SEER) database for clinical cancer research. A comprehensive bibliometric study is required to analyze the tendency of Chinese scholars to utilize the SEER database for clinical cancer research and provide a reference for the future of big data analytics. Objectiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Previously, bibliometric analysis has been employed to capture the raising concerns in public health sector, particularly for monkeypox [11], malaria [12], and Streptococcus pneumoniae vaccination [13]. In the case of cancer, bibliometric has also been employed for several countries, such as China [14], Middle East and North Africa Region [15], and South Africa [16]. None of the previous published studies reported the use of this simple and rapid analysis to understand the cancer epidemiology in Indonesia, suggesting the novelty of the present study.…”
Section: Original Articlementioning
confidence: 99%
“…Previously, bibliometric analysis has been employed to capture the raising concerns in public health sector, particularly for monkeypox [11], malaria [12], and Streptococcus pneumoniae vaccination [13]. In the case of cancer, bibliometric has also been employed for several countries, such as China [14], Middle East and North Africa Region [15], and South Africa [16]. None of the previous published studies reported the use of this simple and rapid analysis to understand the cancer epidemiology in Indonesia, suggesting the novelty of the present study.…”
Section: Original Articlementioning
confidence: 99%
“…Various studies have used keywords search index criteria (Chen et al, 2017;Maier et al, 2020;Kumar et al, 2022;Leong et al, 2021;Pesta et al, 2018;Singh et al, 2022) for extracting the Scopus metadata. It has prepared the base and design for data collection, which has also been used in the present study.…”
Section: Data Collectionmentioning
confidence: 99%
“…Journal performance, development and content insights can be helpful for researchers in studying a specific journal ( Ratten et al, 2020 ). Recently, bibliometric analyses have been conducted in quality journals in the areas of nursing ( Yanbing et al, 2020 ), money laundering ( Saxena & Kumar, 2023 ), tourism ( Leong et al, 2021 ), hospitality ( Martorell Cunill et al, 2019 ), engineering ( Modak et al, 2020 ), medicare ( Lin et al, 2020 ), humanities ( Nwagwu & Egbon, 2011 ) and management ( Ratten et al, 2020 ). For every top-ranked journal, whether the “International Journal of Hospitality Management” or “International Marketing Review,” a bibliometric analysis study has been performed.…”
Section: Introductionmentioning
confidence: 99%